Crimes de linguagem: reflexões sobre criminalização discursiva em redes sociais brasileiras - Lenhardt, Jordana (Language and Law / Linguagem e Direito, 2019)
This study, which is the initial phase of a doctoral research project, sets out to investigate the use of language and the possibility of committing discursive crimes on Brazilian social networks. I analyze a series of extracts from ruling of the 2016.01.1.062108-0 in a lawsuit, which involves an image of one of the current Federal Supreme Court Justices, Gilmar Ferreira Mendes. The defendant was a famous journalist and actress, Monica Iozzi. My analysis uses Systemic-Functional Linguistics (Halliday, 1994; Halliday and Matthiessen, 2004), more precisely the Transitivity System of Ideational Metafunction, and intends to contribute to reflections on language crimes and the possibility of criminalizing the use of language on social networks. Through the analytical results presented in this specific case, it is possible to perceive that the possibility of criminalization of a given discourse encompasses social issues beyond the use of certain lexico-grammatical items, for example the social status of the parties involved, the relations that such linguistic items can establish and the reach of social media.